Veículos elétricos: Como a China está se preparando para se tornar a maior potência mundial do segmento? - Scarlett Queen Almeida Bispo; Alícia Cechin (Instituto de Pesquisa Econômica Aplicada (IPEA), 2023)
– The concern around climate change as a global policy guideline within the United Nations has brought about numerous transformations in sectors directly related to greenhouse gas emissions such as energy and transport. Given this scenario, the objective of the study is to make a global overview of the electric vehicle market, emphasizing China's position in this segment, in order to understand its trajectory from the analysis of the country's development policies such as the "Made in China 2025" and the 13th and 14th Five-Year Plan, as well as specific industry electrification policies. With regard to the results found, it is clear that China, the United States and European countries are the main sellers and holders of battery electric vehicles and plug-in hybrid electric vehicles. Moreover, with regard to the Chinese economy, while it is considered an important environment for the development of electric vehicles, due to its large consumer market as well as its market opening for important car manufacturers through joint ventures, it has also demonstrated ambitious goals to become the biggest industrial power of electric vehicles, with national companies that are a reference not only in the domestic market, but throughout the world.
Keywords: O1; O14; O3; 330; development policies; China; electric vehicles; innovation; climate change